2014
DOI: 10.12816/0023997
|View full text |Cite
|
Sign up to set email alerts
|

Selected Enteropathogens and Clinical Course in Children Hospitalized with Severe Acute Gastroenteritis in Barbados

Abstract: Abstract:Objectives: The primary aim of this study was to determine the prevalence of selected bacterial and viral enteropathogens in children hospitalized with acute gastroenteritis and the secondary aim was to characterize the clinical course and the outcome. Methodology:A retrospective audit of children (<15 years) admitted with acute gastroenteritis during January 2008 to October 2010. Stool samples were analyzed for bacterial pathogens and for the Rotavirus. Demographics, clinical presentations, hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
3
1
Order By: Relevance
“…In contrast, studies from the US (42%) and Shangai (17.2%) reported NTS as the leading cause of bacterial enteric illness, which was much higher than that reported in our study (15,28). Similarly, a study from the West Indies reported a higher rate of NTS (21.1%) compared to our results (29).…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast, studies from the US (42%) and Shangai (17.2%) reported NTS as the leading cause of bacterial enteric illness, which was much higher than that reported in our study (15,28). Similarly, a study from the West Indies reported a higher rate of NTS (21.1%) compared to our results (29).…”
Section: Discussioncontrasting
confidence: 99%
“…The rise of multidrug-resistant (MDR, resistance to three or more classes of antimicrobials) bacteria poses a serious threat to public health ( Kumar et al, 2014 ; Jain et al, 2020 ). Salmonella is one of the common pathogens that can cause bacterial intestinal infections and diarrhea in developed and developing countries ( Lokken et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Maria et al [1] while reviewing foodborne diseases in the Caribbean reported Salmonella spp. as the main cause of the disease in Trinidad and Tobago [2], Dominica [3], St. Lucia [4], Grenada [5], and Barbados [6]. Reptiles including various species of tortoises have been shown to carry zoonotic pathogens including Salmonella spp.…”
Section: Introductionmentioning
confidence: 99%